KKN Tematik Bela Negara Edukasi Pengolahan Gummy Candy sebagai Optimalisasi Tanaman Obat Tradisional di Desa Jati - Kenyo Nitis Nur Kartini; Andani Rizki Putri; Prisca Aglisia Christy; Alya Dewanti Permatasari; Nabila Putri Nuraini; Rohananda Abdan Faiq; Muhammad Zidan Maulana; M Rafi Naufal Fawwaz; Tukiman Tukiman (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
The Community Service Program, which is being carried out by KKN students from the National Development University "Veteran" East Java, aims to provide knowledge and practical skills to the community, particularly PKK mothers RW 03 Babatan Jati Village, Sidoarjo, in processing traditional medicinal plants, ginger, into high-value products, namely gummy candy. This session included a firsthand demonstration of the gummy candy-making process, with ginger extract as the key ingredient. The outcomes of this exercise demonstrated that the participants were quite enthusiastic, as seen by their active engagement in discussions and activities. The finished product was gummy candy with a unique ginger scent and a chewy texture, which is expected to generate new economic prospects in the local community. This initiative is also designed to increase community welfare and develop relationships between students and the local population.